Maternal Programming of Reproductive Function and Behavior in the Female Rat - Cameron, Nicole M. (Frontiers in Evolutionary Neuroscience, 2011)
Parental investment can be used as a forecast for the environmental conditions in which offspring will develop to adulthood. In the rat, maternal behavior is transmitted to the next generation through epigenetic modifications such as methylation and histone acetylation, resulting in variations in estrogen receptor alpha expression. Natural variations in maternal care also influence the sexual strategy adult females will adopt later in life. Lower levels of maternal care are associated with early onset of puberty as well as increased motivation to mate and greater receptivity toward males during mating. Lower levels of maternal care are also correlated with greater activity of the hypothalamus-pituitary-gonadal axis, responsible for the expression of these behaviors. Contrary to the transition of maternal care, sexual behavior cannot simply be explained by maternal attention, since adoption studies changed the sexual phenotypes of offspring born to low caring mothers but not those from high caring dams. Indeed, mothers showing higher levels of licking/grooming have embryos that are exposed to high testosterone levels during development, and adoption studies suggest that this androgen exposure may protect their offspring from lower levels of maternal care. We propose that in the rat, maternal care and the in utero environment interact to influence the reproductive strategy female offspring display in adulthood and that this favors the species by allowing it to thrive under different environmental conditions.